2016
DOI: 10.1002/ajh.24533
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristics, chromosomal alterations, and treatment affecting prognosis of deletion 17p in newly diagnosed myeloma

Abstract: Deletion 17p13, del(17p), is associated with poor outcome in myeloma but some patients show long-term survival. With the current study we intended to identify factors impacting outcome of such high risk patients. We analyzed 110 newly diagnosed, symptomatic patients with del(17p) detected by fluorescence in situ hybridization (FISH) in CD138-purified myeloma cells to identify prognostic factors for survival. Age >65 years, ISS III, and elevated LDH negatively impacted survival. Patients with subclonal (10-60% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 23 publications
2
27
1
1
Order By: Relevance
“…It has been recently suggested that the clone size plays major role in prognosis of patients with del(17p). The patients with 10%‐60% of del(17p) were shown to have longer survival as published by Merz et al21 in their recent work. An et al22 suggested similar cutoff of 50% in their work.…”
Section: Discussionmentioning
confidence: 51%
“…It has been recently suggested that the clone size plays major role in prognosis of patients with del(17p). The patients with 10%‐60% of del(17p) were shown to have longer survival as published by Merz et al21 in their recent work. An et al22 suggested similar cutoff of 50% in their work.…”
Section: Discussionmentioning
confidence: 51%
“…The impact of this variability on clinical outcomes has been uncertain with the importance having been addressed by only a few research groups. 1,8,9 The…”
Section: 7mentioning
confidence: 99%
“…1,8,9 Experimentally the value for the number of positive cells in this test was established based on the background detection rate of false positive signals in cells lacking the abnormality. In clinical studies it is clear that del17p is present at different percentages within the plasma cell population.…”
Section: 7mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, recent studies in patients with deletion 17p demonstrated that higher cutoffs for the aberration (eg, 60% instead of 10% as in our routine practice) resulted in significantly shorter PFS, whereas results for OS were less significant. 20,21 In that context, longitudinal iFISH analyses might help identify distinct clones that are susceptible to certain agents. 22 In line with that hypothesis, we show that bortezomib might overcome the poor prognostic impact of gain 1q21 and deletion 17p if there are no additional subclones.…”
mentioning
confidence: 99%